Capacity Development Of The Women's Empowerment And Child Protection Office In Implementing Children's Appropriate Programs And Activities In Bengkalis District - Rahman, Khairul; Yuliana, Yeni; Wati, Pitri (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
This research examines the capacity building of the Office of Women's Empowerment and Child Protection inimplementing child-friendly programs and activities. Regional government capacity development always contains an understanding of various efforts to improve service performance to the community (Dwi Ratnasari dkk., 2019) This studyaims to analyze the capacity building of the Office of Women's Empowerment and Child Protection in implementingchild-friendly programs and activities in Bengkalis Regency. This type of research is descriptive with a qualitativemethod, namely research that seeks to describe the object or subject under study as it is, and to explain variables and indicators. The results of research regarding the capacity building of the Office of Women's Empowerment and ChildProtection in implementing child- friendly programs and activities were analyzed through four indicators. First,individual indicators are not in a good enough category because not all employees work according to their fields. Second, the organizational indicators in compiling a vision, strategy and structure that can support the development ofBengkalis Regency to become a Child-friendly District are appropriate, it's just that the work culture created has notcontributed to the implementation of child-friendly programs and activities. Third, the infrastructure indicators with thefacilities and infrastructure built are in accordance with the needs of each cluster that supports the development of Child-Friendly Districts, it's just that not all regions in Bengkalis Regency can feel this. Fourth, the networkingindicators carried out by the Office of Women's Empowerment and Child Protection are quite good with coordination involving various cross-sectors and comparisons with regions that have achieved the title of Child-FriendlyRegency/City even though they have not been implemented optimally for the development of Child-Friendly Districts and supervision carried out in child-friendly programs and activities is still minimal.